Thick copper plate etching solution and etching method thereof
By adding tetraphenyl porphyrin zinc to the etching solution of the super-thick copper multi-layer printed board and using a cleaning solution containing surfactant, the problem of uneven copper surface was solved, and the semi-cured sheet was prepared by solvent-free method for pressing The circuit performance and reliability of thick copper plates are improved.
Patent Information
- Application Number
- CN202411594427.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-09
- Publication Date
- 2025-02-18
AI Technical Summary
During the etching process of ultra-thick copper multi-layer printed boards, existing acid etching liquid can easily cause uneven copper surfaces, resulting in some conical copper particles, protrusions and obvious gaps in height.
By adding tetraphenyl porphyrin zinc as an additive to the etching solution, the copper surface etching effect is improved, and after etching, cleaning is performed using a cleaning solution containing surfactant, thereby reducing residual materials and defects. At the same time, the solvent-free method is used to prepare semi-cured sheets for pressing, which improves the circuit performance and reliability of thick copper plates.
The addition of tetraphenylporphyrin zinc significantly improves the uniformity and smoothness of the etching layer, reduces pinholes and bubbles, and improves the plating quality. The semi-cured sheet prepared by the solvent-free method is simple in the process, with less pollution, and the thick copper plate circuit performance and reliability are better.
Smart Images

Figure BDA0005126433120000081
Abstract
Description
Technical Field
[0001] The invention belongs to the field of circuit boards, and particularly designs a thick copper plate etching liquid and an etching method thereof. Background Art
[0002] Ultra-thick copper multilayer printed circuit board is a special type of printed circuit board. The main features of this type of printed circuit board are that the number of layers is generally 4 to 12, the thickness of the inner substrate copper foil is ≥3500m (100z), and the quality reliability requirements are high. Ultra-thick copper multilayer printed circuit board has good current carrying capacity and excellent heat dissipation. It is mainly used in network energy, communications, automobiles, high-power power supplies, clean energy solar energy, etc., so it has broad market development prospects.
[0003] Etching is the process of removing the parts of the film (thickness is tens to hundreds of nanometers) deposited before photolithography that are not covered and protected by the photoresist by chemical or physical means, in order to achieve the purpose of transferring the mask pattern to the film.
[0004] Acidic etching liquid for printed circuit boards needs to be added with specific additives, and the additives mainly refer to organic compounds. Different types of additives play different roles in the etching process, such as pH regulators, accelerators, etc. In the etching process, there will be large fluctuations and unevenness of the etching surface, and there will be some conical copper particles, protrusions and obvious height differences. Studies have shown that porphyrin additives may improve the etching effect of etching liquid through their unique chemical properties. Porphyrin additives can help to remove the material surface more evenly and reduce the unevenness and defects in the etching process. The present invention improves the above problems by adding porphyrin additives.
[0005] In order to balance the cleaning effect and corrosion resistance, the post-etching residue cleaning liquid products currently used in integrated circuit manufacturing generally contain hydroxylamine, organic solvents, corrosion inhibitors and water, all of which show good cleaning effects and reduce the defects caused by residues on the surface of the circuit board.
[0006] Traditional epoxy glass fiber cloth prepreg is mainly composed of epoxy resin, curing agent, accelerator, diluent, filler and solvent. The preparation relies on the volatilization of solvent during heating. This preparation method not only pollutes the environment, but also the residual solvent affects the quality of prepreg and the performance of copper clad laminate. Therefore, exploring the preparation technology of solvent-free epoxy prepreg is the most important task and difficulty of copper clad laminate industry.
[0007] Xylene diisocyanate is widely used in the adhesive field as a curing agent. It has high reactivity and excellent chemical stability, but there are also some problems in use. It is sensitive to moisture, has high volatility and has certain irritation. Therefore, selecting a suitable accelerating curing agent to combine with it to improve the curing effect is the research focus of the present invention. Summary of the invention
[0008] In order to solve the above technical problems, the specific preparation process of the present invention is as follows:
[0009] The etching solution includes: 60-80 parts of cupric chloride, 120-160 parts of hydrochloric acid, 40-80 parts of sodium chloride, 100-150 parts of ammonium chloride, 5-10 parts of ethylenediaminetetraacetic acid, 10-20 parts of sodium acetate, 50-100 parts of sodium nitrate, 8-15 parts of polyethylene glycol, 1.2-3.5 parts of porphyrin additive, dissolved in 1000 parts of deionized water;
[0010] Wherein, the porphyrin additive is tetraphenylporphyrin zinc.
[0011] Evenly coat the photosensitive adhesive on the copper plate after grinding and roughening to form a 4.5-6μm film, and then expose it after standing for 10-15 minutes;
[0012] Place the circuit pattern to be etched in the exposure machine, overlap the photosensitive adhesive and the copper plate, and then expose the pattern on the film to the ultraviolet lamp for 8-10 minutes to solidify the photosensitive adhesive. After exposure, let it stand in a dark room for 25-30 minutes and then send it to the developing tank for development for 8-10 minutes. Wash and dry it to obtain the copper substrate to be etched;
[0013] Add the above etching solution into the etching solution tank, fix the copper substrate to be etched on the spray etching machine for etching, keep the etching solution temperature at 30-45°C, adjust the spray pressure to 0.05-0.2MPa, and the spray time to 8-12min, then spray the cleaning solution for 8-10min, and then brownize, fill the circuit surface with bisphenol A type epoxy resin 128, 36T mesh, and print 20mm thick scraper twice, the scraper is 30° with the board direction, and the pressure angle with the board is 15°-20°. After printing, place it horizontally for two hours, bake it horizontally at 80° for 45min, and then bake it at 120° for 30min; then add 1-3 prepregs between the two layers of copper plates that have been baked by riveting to obtain thick copper plates for standby use;
[0014] The cleaning solution contains 2-10% of a surfactant.
[0015] The surfactant is N-methylhydroxyacetanilide.
[0016] The semi-cured sheet is prepared by a solvent-free process: 100-120 parts of bisphenol A epoxy resin 128 and 25-35 parts of phenolic epoxy resin 704 are weighed respectively, put into a fixed iron frame ring, and heated at a constant temperature in a constant temperature water bath at 60°C, with a rotation speed of 300-500rpm, and stirred for 20-30min, and then 4-9% of a xylene diisocyanate curing agent and a certain amount of a curing accelerator are added, the rotation speed is 300-500rpm, heated to 90°C, and stirred for 5-10min to obtain a glue solution, and the prepared glue solution is evenly rolled on a glass fiber cloth by a casting method, with a pressure of 1Mpa and a temperature of 130°C, and maintained for 15min to obtain a semi-cured sheet.
[0017] The curing accelerator is 1-methyl-4-carboxylic acid imidazole hydrochloride, and the added amount is 3-12% of the curing agent.
[0018] The method of riveting is to add 1-3 prepregs between the two layers of the baked copper plates for pressing. The specific process is: on a double-roll calender, the copper plate and the prepreg are riveted, the roller temperature is adjusted to 90°C, the heating rate is 15°C / min to 130°C, the pressure is 5Mpa, and maintained for 15 minutes, and then the heating rate is continued to be 15°C / min to 180°C, the pressure is 20Mpa, and maintained for 60 minutes, so as to obtain a thick copper plate for use.
[0019] The beneficial effects of the present invention are:
[0020] 1. The present invention relates to a thick copper plate etching solution and an etching method thereof. In the acidic etching solution, a suitable porphyrin additive is selected to improve the undulation and unevenness of the copper surface and improve the roughness. After etching, a cleaning solution containing a surfactant is used to clean the copper surface to reduce residual substances and defects. A solvent-free method is used to prepare a prepreg to press the copper plate. The process is simple and less polluting, and the obtained thick copper plate circuit has better performance and reliability.
[0021] 2. The four phenyl structures of tetraphenylporphyrin zinc in the porphyrin additive in the etching solution provide extensive π-π interactions and strong electron-accepting ability, making its adsorption on the surface of the copper layer more stable and effective. This strong adsorption ability helps to better control the uniformity and smoothness of the etching layer. It forms positively charged NH3+ in the electrolyte, which attracts the negatively charged protrusions on the copper layer, thereby inhibiting high-position copper electrodeposition.
[0022] 3. The addition of zinc tetraphenylporphyrin can improve the dispersibility and current efficiency of the electro-etching solution, thereby improving the thickness and uniformity of the etching layer. At the same time, it can effectively reduce pinholes and bubbles in the etching layer, making the coating quality more stable. The adsorption layer formed by zinc tetraphenylporphyrin and chloride ions occupies more and more positions on the copper surface, which strengthens the inhibition of copper grain electrodeposition, refines the grains, inhibits the growth of copper particles that grow too fast and are large in size, and reduces the roughness, making the surface of the copper etching layer less undulating, smooth, and less rough, and the surface morphology of the electroplated copper coating is better.
[0023] 4. After adding appropriate tetraphenylporphyrin zinc, due to the unsaturated bonds contained in the tetraphenylporphyrin zinc additive, its strong ability to accept electrons enhances its ability to adsorb on the surface of the copper layer. The addition of tetraphenylporphyrin zinc enhances the dispersibility of the electro-etching liquid, has high current efficiency, high etching layer efficiency, high process stability, and significantly improves the uniformity and durability of the etching layer. It also helps to extend the service life of the product and has environmental advantages.
[0024] 5. The π electron cloud on the aromatic ring in N-methylhydroxyacetanilide has a high electron density and can interact with other components in the cleaning solution. This electronic effect helps to improve the effectiveness of the corrosion inhibitor, especially the protection of aluminum metal. The electron cloud of the aromatic ring can stabilize the oxide film on the metal surface, thereby slowing down the corrosion process. The hydroxyl group in N-methylhydroxyacetanilide can hydrogen bond with the residue in the cleaning solution and the substrate surface, enhancing the wettability and adhesion of the cleaning solution. This enhanced wettability helps to improve the removal efficiency of the residue after dry etching. The acetyl group can adjust the surface tension and viscosity of the liquid by interacting with surfactants or other components in the cleaning solution. This helps to improve the fluidity of the cleaning solution and its ability to cover complex surfaces. In addition, N-methylhydroxyacetanilide has good water solubility, and the residue can be effectively removed by water in the subsequent use, reducing pollution, simplifying the subsequent processing process, and reducing the subsequent processing cost.
[0025] 6. The solvent-free process for preparing curing agent improves thermal stability and glass transition temperature, solves the problems of environmental pollution and poor weather resistance existing in the traditional solvent method, and makes the preparation process more environmentally friendly and efficient.
[0026] 7.1-Methyl-4-carboxylic acid imidazole hydrochloride is added as a curing accelerator, which can effectively reduce the formation of oligomers and improve the overall quality of copper clad laminates. First, it can reduce the curing temperature of the original system, and the water resistance and heat aging resistance are also increased. Among them, 1-methyl-4-carboxylic acid imidazole hydrochloride forms a stable curing network with the curing agent, thereby improving the moisture stability of the curing system and reducing the volatility of the curing agent. 1-Methyl-4-carboxylic acid imidazole hydrochloride has excellent curing and promotion effects, which can greatly reduce the curing temperature of the curing system, and improve the moisture resistance and high volatility of the xylene diisocyanate curing agent, improve the solder resistance, peel strength and breakdown voltage of the thick copper plate, thereby improving the performance and reliability of the circuit board, and can also reduce production costs and extend the service life of the product. DETAILED DESCRIPTION
[0027] The present invention is further described in detail below with reference to the embodiments.
[0028] The glass fiber cloth used in the embodiment of the present invention is alkali-free glass fiber cloth 1080, which was purchased from Taizhou Zhongsheng Fiberglass Products Co., Ltd. The raw materials or chemical reagents used in the embodiment of the present invention, unless otherwise specified, are obtained through conventional commercial channels. The specifications of the copper substrates used below are all FR-1.
[0029] Example 1
[0030] The photosensitive adhesive was evenly coated on the copper plate after the grinding plate roughening to form a 5.2μm film, and then exposed after standing for 12 minutes;
[0031] Place the circuit pattern to be etched in the exposure machine, overlap the photosensitive adhesive and the copper plate, and then expose the pattern on the film to the ultraviolet lamp for 9 minutes to solidify the photosensitive adhesive. After exposure, let it stand in a dark room for 28 minutes and then send it to the developing tank for development for 9 minutes. Wash it and dry it to obtain the copper substrate to be etched;
[0032] Add 70 parts of copper chloride, 140 parts of hydrochloric acid, 60 parts of sodium chloride, 125 parts of ammonium chloride, 7 parts of ethylenediaminetetraacetic acid, 15 parts of sodium acetate, 80 parts of sodium nitrate, 12 parts of polyethylene glycol, and 2.4 parts of tetraphenylporphyrin zinc into the etching solution tank, and dissolve them in 1000 parts of deionized water. Fix the copper substrate to be etched on the spray etcher for etching, keep the etching solution temperature at 38°C, adjust the spray pressure to 0.12MPa, and the spray time to 10min;
[0033] Example 2
[0034] The photosensitive adhesive was evenly coated on the copper plate after grinding and roughening to form a 4.5 μm film, and then exposed after standing for 15 minutes;
[0035] Place the circuit pattern to be etched in the exposure machine, overlap the photosensitive adhesive and the copper plate, and then expose the pattern on the film to the ultraviolet lamp for 10 minutes to solidify the photosensitive adhesive. After exposure, let it stand in a dark room for 25 minutes and then send it to the developing tank for development for 10 minutes. Wash and dry it to obtain the copper substrate to be etched;
[0036] Add 60 parts of copper chloride, 160 parts of hydrochloric acid, 40 parts of sodium chloride, 150 parts of ammonium chloride, 10 parts of ethylenediaminetetraacetic acid, 10 parts of sodium acetate, 100 parts of sodium nitrate, 15 parts of polyethylene glycol, and 3.5 parts of tetraphenylporphyrin zinc into the etching solution tank, and dissolve them in 1000 parts of deionized water. Fix the copper substrate to be etched on the spray etcher for etching, keep the etching solution temperature at 30°C, adjust the spray pressure to 0.2MPa, and the spray time to 8min;
[0037] Example 3
[0038] The photosensitive adhesive was evenly coated on the copper plate after the grinding plate roughening to form a 6μm film, and then exposed after standing for 10 minutes;
[0039] Place the circuit pattern to be etched in the exposure machine, overlap the photosensitive adhesive and the copper plate, and then expose the pattern on the film to the ultraviolet lamp for 8 minutes to solidify the photosensitive adhesive. After exposure, let it stand in a dark room for 30 minutes and then send it to the developing tank for 8 minutes. Wash and dry it to obtain the copper substrate to be etched;
[0040] Add 80 parts of copper chloride, 120 parts of hydrochloric acid, 80 parts of sodium chloride, 100 parts of ammonium chloride, 5 parts of ethylenediaminetetraacetic acid, 20 parts of sodium acetate, 50 parts of sodium nitrate, 8 parts of polyethylene glycol, and 1.2 parts of tetraphenylporphyrin zinc into the etching solution tank, and dissolve them in 1000 parts of deionized water. Fix the copper substrate to be etched on the spray etcher for etching, keep the etching solution temperature at 45°C, adjust the spray pressure to 0.05MPa, and the spray time to 12min;
[0041] Comparative Example 1
[0042] The difference between this comparative example and Example 1 is that the tetraphenylporphyrin zinc is sodium polydisulfide dipropane sulfonate, and the rest of the implementation manner is the same as Example 1.
[0043] Comparative Example 2
[0044] The difference between this comparative example and Example 1 is that the tetraphenylporphyrin zinc is tetraphenylporphyrin tetrasulfonic acid, and the rest of the implementation manner is the same as Example 1.
[0045] Comparative Example 3
[0046] The difference between this comparative example and Example 1 is that in this comparative example, tetraphenylporphyrin zinc is not added to the etching solution, and the rest of the implementation is the same as Example 1.
[0047] Comparative Example 4
[0048] The difference between this comparative example and Example 1 is that the amount of tetraphenylporphyrin zinc added is different, specifically: 70 parts of cupric chloride, 140 parts of hydrochloric acid, 60 parts of sodium chloride, 125 parts of ammonium chloride, 7 parts of ethylenediaminetetraacetic acid, 15 parts of sodium acetate, 80 parts of sodium nitrate, 12 parts of polyethylene glycol, 4.8 parts of tetraphenylporphyrin zinc are added to the etching solution tank, and dissolved in 1000 parts of deionized water, and the copper substrate to be etched is fixed on the spray etcher for etching, the etching solution temperature is maintained at 38°C, the spray pressure is adjusted to 0.12MPa, and the spray time is 10min; the rest is the same as Example 1.
[0049] Comparative Example 5
[0050] The difference between this comparative example and Example 1 is that the amount of tetraphenylporphyrin zinc added is different, specifically: 70 parts of cupric chloride, 140 parts of hydrochloric acid, 60 parts of sodium chloride, 125 parts of ammonium chloride, 7 parts of ethylenediaminetetraacetic acid, 15 parts of sodium acetate, 80 parts of sodium nitrate, 12 parts of polyethylene glycol, and 0.5 parts of tetraphenylporphyrin zinc are added to the etching solution tank, and dissolved in 1000 parts of deionized water, and the copper substrate to be etched is fixed on the spray etcher for etching, the etching solution temperature is maintained at 38°C, the spray pressure is adjusted to 0.12MPa, and the spray time is 10min; the rest is the same as Example 1.
[0051] Performance Test:
[0052] Etching rate: the depth to which the etching solution dissolves the metal per unit time or the time required to dissolve a certain thickness of metal.
[0053] Roughness test: The samples obtained in Examples 1-3 and Comparative Examples 1-5 were cut into a size of 10 mm x 10 mm, first cleaned with 5% sulfuric acid, then cleaned with alcohol and blown dry, and three points of each sample were measured using an OIYMPUS LEXTOLS5100 laser scanning microscope. Each point was spliced with three horizontal regions, and the average value of Rz (the distance between the top line of the wheel peak and the bottom line of the valley, μm) was taken. The results are shown in Table 1.
[0054] Table 1 Performance test
[0055] Etching solution Etching rate (μm / min) Roughness Rz(μm) Example 1 32.5 0.448 Example 2 31.8 0.487 Example 3 31.9 0.469 Comparative Example 1 23.8 1.108 Comparative Example 2 26.5 0.865 Comparative Example 3 18.8 1.403 Comparative Example 4 30.1 0.524 Comparative Example 5 28.6 0.635
[0056] The following examples are all carried out on the basis of Example 1:
[0057] Example 4
[0058] Then, the cleaning liquid was sprayed and cleaned for 9 minutes. The cleaning liquid was a cleaning liquid containing 6% N-methylhydroxyacetanilide. Then, browning was performed. Bisphenol A epoxy resin 128 was filled into the circuit surface. 36T mesh was used. 20mm thick scraper printing was performed twice. The scraper was 30° to the board direction and 18° to the board pressure angle. After printing, it was placed horizontally for two hours, placed horizontally at 80° and baked for 45 minutes, and then baked at 120° for 30 minutes.
[0059] Preparation of semi-cured sheet by solvent-free process: 110 parts of bisphenol A epoxy resin 128 and 30 parts of phenolic epoxy resin 704 were weighed respectively, put into a fixed iron frame ring, and heated in a constant temperature water bath at 60°C at a speed of 400 rpm. After stirring for 25 minutes, 7% of xylene diisocyanate curing agent and 0.62% of 1-methyl-4-carboxylic imidazole hydrochloride were added, the speed was 400 rpm, heated to 90°C, stirred for 8 minutes, and the glue solution was obtained. The prepared glue solution was evenly rolled on the glass fiber cloth by a casting method at a pressure of 1 MPa and a temperature of 130°C. The semi-cured sheet was obtained by maintaining it for 15 minutes.
[0060] Then, two semi-cured sheets are added between the two layers of copper plates that have been baked by riveting for pressing. On a double-roll calender, the copper plate and the semi-cured sheet are riveted, the roller temperature is adjusted to 90°C, the heating rate is increased to 130°C at 15°C / min, the pressure is 5Mpa, and maintained for 15 minutes, and then the heating rate is continued to be increased to 180°C at 15°C / min, the pressure is 20Mpa, and maintained for 60 minutes, and the thick copper plate is obtained for use.
[0061] Example 5
[0062] Then, the cleaning liquid was sprayed and cleaned for 10 minutes. The cleaning liquid was a cleaning liquid containing 10% N-methylhydroxyacetanilide. Then, browning was performed. Bisphenol A epoxy resin 128 was filled into the circuit surface. 36T mesh was used. 20mm thick scraper printing was performed twice. The scraper was 30° to the board direction and 15° to the board pressure angle. After printing, it was placed horizontally for two hours, placed horizontally at 80° and baked for 45 minutes, and then baked at 120° for 30 minutes.
[0063] Preparation of semi-cured sheet by solvent-free process: 120 parts of bisphenol A epoxy resin 128 and 25 parts of phenolic epoxy resin 704 were weighed respectively, put into a fixed iron frame ring, and heated in a constant temperature water bath at 60°C at a speed of 500 rpm. After stirring for 20 minutes, 9% of xylene diisocyanate curing agent and 0.16% of 1-methyl-4-carboxylic imidazole hydrochloride were added, the speed was 300 rpm, heated to 90°C, stirred for 10 minutes, and the glue solution was obtained. The prepared glue solution was evenly rolled on the glass fiber cloth by a casting method at a pressure of 1 MPa and a temperature of 130°C. The semi-cured sheet was obtained by maintaining it for 15 minutes.
[0064] Then, three semi-cured sheets are added between the two layers of copper plates that have been baked by riveting for pressing. On a double-roll calender, the copper plate and the semi-cured sheet are riveted, the roller temperature is adjusted to 90°C, the heating rate is increased to 130°C at 15°C / min, the pressure is 5Mpa, and maintained for 15 minutes, and then the heating rate is continued to be increased to 180°C at 15°C / min, the pressure is 20Mpa, and maintained for 60 minutes, and the thick copper plate is obtained for use.
[0065] Example 6
[0066] Then, the cleaning liquid was sprayed for 8 minutes. The cleaning liquid was a cleaning liquid containing 2% N-methylhydroxyacetanilide. Then, browning was performed. Bisphenol A epoxy resin 128 was filled into the circuit surface. 36T mesh was used. 20mm thick scraper printing was performed twice. The scraper was 30° to the board direction and 20° to the board pressure angle. After printing, it was placed horizontally for two hours, placed horizontally at 80° and baked for 45 minutes, and then baked at 120° for 30 minutes.
[0067] Preparation of semi-cured sheet by solvent-free process: 100 parts of bisphenol A epoxy resin 128 and 25-35 parts of phenolic epoxy resin 704 were weighed respectively, put into a fixed iron frame ring, and heated at a constant temperature of 60°C in a constant temperature water bath at a speed of 300 rpm. After stirring for 30 minutes, 4% of xylene diisocyanate curing agent and 1.08% of 1-methyl-4-carboxylic imidazole hydrochloride were added, the speed was 500 rpm, heated to 90°C, stirred for 5 minutes, and the prepared glue was evenly rolled on the glass fiber cloth by a casting method at a pressure of 1 MPa and a temperature of 130°C. The semi-cured sheet was obtained by maintaining it for 15 minutes.
[0068] Then, a semi-cured sheet is added between the two layers of copper plates that have been baked by riveting for pressing. On a double-roll calender, the copper plate and the semi-cured sheet are riveted, the roller temperature is adjusted to 90°C, the heating rate is increased to 130°C at 15°C / min, the pressure is 5Mpa, and maintained for 15min, and then the heating rate is continued to be increased to 180°C at 15°C / min, the pressure is 20Mpa, and maintained for 60min, and the thick copper plate is obtained for use.
[0069] Comparative Example 6
[0070] The difference between this comparative example and Example 4 is that the cleaning liquid in this comparative example is deionized water, and the rest is the same as Example 4.
[0071] Comparative Example 7
[0072] The difference between this comparative example and Example 4 is that the cleaning liquid in this comparative example is A4625B cleaning liquid, and the rest is the same as Example 4.
[0073] Comparative Example 8
[0074] The difference between this comparative example and Example 4 is that the cleaning solution in this comparative example is a cleaning solution containing 20% N-methylhydroxyacetanilide; the rest is the same as Example 4.
[0075] Comparative Example 9
[0076] The difference between this comparative example and Example 4 is that the cleaning solution in this comparative example is a cleaning solution containing 1% N-methylhydroxyacetanilide; the rest is the same as Example 4.
[0077] Test 2: Ionic contamination detection
[0078] The copper substrates cleaned after etching in the above-mentioned Examples 4-6 and Comparative Examples 6-7 were cleaned and the resistivity of the collected liquid was measured (China Ministry of Information Industry SJ20883-2003 Cleaning process method for printed circuit board components after soldering, 2204), and the sodium chloride content per unit area representing the degree of contamination of the printed circuit board was calculated as Wr, ug / cm 2 . It is calculated as follows:
[0079]
[0080] Where h is the position scale of the wave surface of the extract in the test tank; m is the total amount of sodium chloride contained in the collected liquid, ug; S is the area of the tested sample, cm 2
[0081] Table 2 Cleanliness test
[0082] Group <![CDATA[Cleanliness (ug / cm 2 )]]> Example 4 0.047 Example 5 0.048 Example 6 0.052 Comparative Example 6 0.164 Comparative Example 7 0.125 Comparative Example 8 0.060 Comparative Example 9 0.086
[0083] Comparative Example 9
[0084] The difference between this comparative example and Example 4 is that 1-methyl-4-carboxylic imidazole hydrochloride is not added in this comparative example, and the rest is the same as Example 4.
[0085] Comparative Example 10
[0086] The difference between this comparative example and Example 4 is that in this comparative example, 1-methyl-4-carboxylic imidazole hydrochloride is 2-ethyl-4-methylimidazole, and the rest is the same as Example 4.
[0087] Comparative Example 11
[0088] The difference between this comparative example and Example 4 is that the amount of 1-methyl-4-carboxylic acid imidazole hydrochloride added in this comparative example is different. The specific solvent-free process for preparing the semi-cured sheet is as follows: 110 parts of bisphenol A epoxy resin 128 and 30 parts of phenolic epoxy resin 704 are weighed respectively, and placed in a fixed iron frame ring and heated at a constant temperature of 60°C in a constant temperature water bath at a speed of 400 rpm. After stirring for 25 minutes, 7% of xylene diisocyanate curing agent and 0.05% of 1-methyl-4-carboxylic acid imidazole hydrochloride are added, the speed is 400 rpm, heated to 90°C, stirred for 8 minutes, and a glue solution is obtained. The prepared glue solution is evenly rolled on the glass fiber cloth by a casting method at a pressure of 1 MPa and a temperature of 130°C. The semi-cured sheet is obtained by maintaining it for 15 minutes; the rest is the same as Example 4.
[0089] Comparative Example 12
[0090] The difference between this comparative example and Example 4 is that the amount of 1-methyl-4-carboxylic acid imidazole hydrochloride added in this comparative example is different. The specific solvent-free process for preparing the semi-cured sheet is as follows: 110 parts of bisphenol A epoxy resin 128 and 30 parts of phenolic epoxy resin 704 are weighed respectively, and placed in a fixed iron frame ring and heated at a constant temperature of 60°C in a constant temperature water bath at a speed of 400 rpm. After stirring for 25 minutes, 7% of xylene diisocyanate curing agent and 0.05% of 1-methyl-4-carboxylic acid imidazole hydrochloride are added, the speed is 400 rpm, heated to 90°C, stirred for 8 minutes, and a glue solution is obtained. The prepared glue solution is evenly rolled on the glass fiber cloth by a casting method at a pressure of 1 MPa and a temperature of 130°C. The semi-cured sheet is obtained by maintaining it for 15 minutes; the rest is the same as Example 4.
[0091] Comparative Example 13
[0092] The difference between this comparative example and Example 4 is that in this comparative example, a semi-cured sheet is added between the two layers of copper plates that have been baked for pressing by riveting. On a double-roll calender, the copper plate and the semi-cured sheet are riveted, the roller temperature is adjusted to 90°C, the heating rate is increased to 180°C at 15°C / min, the pressure is 20Mpa, and the pressure is maintained for 80 minutes to obtain a thick copper plate for use; the rest is the same as Example 4.
[0093] Test 3: Copper plate pressing performance test
[0094] Solder immersion resistance: It is an extremely important non-electrical performance index of the finished circuit board, and has a huge effect on the application of the copper clad laminate. The test method is: the temperature of the heating furnace equipped with a constant temperature controller is adjusted to 288°C, and the prepared solder liquid is placed in the heating furnace. When the temperature of the solder liquid stabilizes to 288°C, the pressed copper clad laminates of Examples 4-6 and Comparative Examples 9-13 are placed in the solder liquid, and the stopwatch is started. When the copper clad laminate in the solder liquid is about to bubble and separate, the stopwatch is stopped, and the recorded time is the bubbling time.
[0095] Peel strength: It indicates the bonding force between the copper foil and the substrate, usually expressed by the force required to tear the copper foil vertically per inch of width. Peel off about 12mm of the copper foil at one edge of Examples 4-6 and Comparative Examples 9-13 from the copper-clad laminate, then fix the sample on the sample holder, and clamp the peeled copper foil with the sample clamp so that the copper foil is perpendicular to the substrate material. Turn on the peeling machine and apply pressure evenly, with the force direction always perpendicular to the substrate material direction. Determine the value when the peeling length is greater than 25mm, and calculate the minimum load required per unit width as the peeling strength, in N / mm.
[0096] Breakdown voltage: Use a high voltage breakdown tester with a voltage increase rate of 500V / s to record the voltage value displayed in the display area of the test instrument when the copper clad laminate is broken down.
[0097] Table 3 Copper plate pressing performance test
[0098] Group Solder immersion time(s) Peel strength (N / mm) Breakdown voltage(kV / mm) Example 4 183 2.4 69 Example 5 181 2.3 68 Example 6 178 2.4 65 Comparative Example 9 94 1.0 35 Comparative Example 10 128 1.5 48 Comparative Example 11 174 2.0 62 Comparative Example 12 153 1.7 54 Comparative Example 13 162 1.8 58
Claims
1. A thick copper plate etching solution, characterized in that: Its components include: 60-80 parts of cupric chloride, 120-160 parts of hydrochloric acid, 40-80 parts of sodium chloride, 100-150 parts of ammonium chloride, 5-10 parts of ethylenediaminetetraacetic acid, 10-20 parts of sodium acetate, 50-100 parts of sodium nitrate, 8-15 parts of polyethylene glycol, 1.2-3.5 parts of porphyrin additive, dissolved in 1000 parts of deionized water; Wherein, the porphyrin additive is tetraphenylporphyrin zinc.
2. An etching method using the thick copper plate etching solution according to claim 1, characterized in that: Evenly coat the photosensitive adhesive on the copper plate after grinding and roughening to form a 4.5-6μm film, and then expose it after standing for 10-15 minutes; Place the circuit pattern to be etched in the exposure machine, overlap the photosensitive adhesive and the copper plate, and then expose the pattern on the film to the ultraviolet lamp for 8-10 minutes to solidify the photosensitive adhesive. After exposure, let it stand in a dark room for 25-30 minutes and then send it to the developing tank for development for 8-10 minutes. Wash and dry it to obtain the copper substrate to be etched; Add the above etching solution into the etching solution tank, fix the copper substrate to be etched on the spray etching machine for etching, maintain the etching solution temperature at 30-45°C, adjust the spray pressure to 0.05-0.2MPa, and the spray time is 8-12min, then spray the cleaning solution for 8-10min, and then brownize; The cleaning solution contains 2-10% of a surfactant.
3. The etching method according to claim 2, wherein: The surfactant is N-methylhydroxyacetanilide.
4. A process for preparing a thick copper plate using the etching method according to claim 2 or 3, characterized in that: Fill the circuit surface of the browned copper substrate with bisphenol A epoxy resin 128, 36T mesh, and print twice with 20mm thick scraper glue. The scraper glue is 30° to the board direction and the pressure angle with the board is 15°-20°. After printing, place it horizontally for two hours, bake it horizontally at 80° for 45 minutes, and then bake it at 120° for 30 minutes. Then, add 1-3 semi-cured sheets between the two layers of copper plates that have been baked by riveting to press them together to obtain a thick copper plate for standby use.
5. A process for preparing a thick copper plate as claimed in claim 4, characterized in that: The semi-cured sheet is prepared by a solvent-free process: 100-120 parts of bisphenol A epoxy resin 128 and 25-35 parts of phenolic epoxy resin 704 are weighed respectively, put into a fixed iron frame ring, and heated at a constant temperature in a constant temperature water bath at 60°C, with a rotation speed of 300-500rpm, and stirred for 20-30min, and then 4-9% of a xylene diisocyanate curing agent and a certain amount of a curing accelerator are added, the rotation speed is 300-500rpm, heated to 90°C, and stirred for 5-10min to obtain a glue solution, and the prepared glue solution is evenly rolled on a glass fiber cloth by a casting method, with a pressure of 1Mpa and a temperature of 130°C, and maintained for 15min to obtain a semi-cured sheet.
6. A process for preparing a thick copper plate as claimed in claim 5, characterized in that: The curing accelerator is 1-methyl-4-carboxylic acid imidazole hydrochloride, and the added amount is 3-12% of the curing agent.
7. A process for preparing a thick copper plate as claimed in claim 4, characterized in that: The method of riveting is to add 1-3 prepregs between the two layers of the baked copper plates for pressing. The specific process is: on a double-roll calender, the copper plate and the prepreg are riveted, the roller temperature is adjusted to 90°C, the heating rate is 15°C / min to 130°C, the pressure is 5Mpa, and maintained for 15 minutes, and then the heating rate is continued to be 15°C / min to 180°C, the pressure is 20Mpa, and maintained for 60 minutes, so as to obtain a thick copper plate for use.